O ato pedagógico como ação dialógica e complexa: aproximações, complementaridades e diferenças entre os pensamentos de Paulo Freire e Edgar Morin - Santos, Ademar Alves dos (2013)
The present Dissertation has as object of research the approaches of possible complementarities and differences that regard to the idea and to the practice of the dialogue that must be present in the educational action. The thoughts of Paulo Freire and Edgar Morin are taken as reference to make it possible to understand the pedagogical act as dialogic action and in particular, from the concepts of dialogue/domination, dialectic/dialogia, complexity/consciousness/awareness, linearity, otherness and freedom/liberation. This literature search was performed from the works of Paulo Freire and Edgar Morin. The work indicates that these theoretical principles that form the basis for dialogical educational action in the two authors have significant conceptual approach although from different matrices. This study aims to offer more subsidies for the perception about the importance of seeking to transform the educational act in authentic a Dialogic practice in order to contribute to an education capable of helping more and more men and women in their process of humanization.